Pengaruh Consumer Demographics, Consumer Shopping Habit, dan Store Attributes pada Pilihan Format Ritel Grocery di Surabaya - Utomo, Melisa Dewi (Kajian Manajemen dan Bisnis, 2010)
The purpose of this study is to investigate the differences of consumer shopping habits in grocery retail and the differences of grocery retail format choice based on consumer demographics. This research also aims to investigate the influence of consumer shopping habits in grocery retail and attributes owned by grocery retail to grocery retail format choice.